Penerapan Pembelajaran Mendalam di Sekolah Dasar untuk Meningkatkan Efektivitas dan Kualitas Pembelajaran IPAS - Luthfiyah, Hullatul; Toto Nusantara; Siti Faizah; Shirly Rizki Kusumaningrum; Mardhatillah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This study explores the implementation of a deep learning approach by IPAS subjects at SD Negeri Sumbertaman 2. It uses a qualitative method with a case study approach involving participatory observation, in-depth interviews, and document analysis. The results show the school’s success in adapting the three main aspects of deep learning according to the local context. The meaningful learning approach is realized through learning that is linked to real problems in the students’ environment, while mindful learning is implemented with structured metacognitive strategies. In addition, joyful learning is implemented by integrating local cultural elements into learning. To overcome the limitations of digital infrastructure, the school develops a hybrid learning model and improves teachers’ capacity through continuous professional development programs. This implementation positively impacts students’ critical thinking skills, strengthening character and social skills according to the “6C” concept and increasing learning motivation. This learning model exemplifies how schools in urban border areas can make meaningful educational transformations by integrating cognitive, social-emotional, and cultural aspects in IPAS learning.